A study of power: the making of the Turkish electricity market - Sözer, Pınar. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2014., 2014)
As a study of power and market-making, this thesis analyzes the political and economic dynamics of the making, maintenance, transformation, consolidation and current state of the Turkish electricity market. It examines the utilization of disciplinary discourses and expert knowledge claims; the manipulation of the dynamics with respect to market power and political power; market tools, devices, and information technologies; and the mechanisms and factors in the price realization from an actor-network perspective, which incorporates multiple market agencies and the active agency of the commodity under analysis. The underlying research is based on an official document analysis that reviews the established legal framework for the marketization of electricity, non-structured and semi-structured in-depth interviews with market actors, and secondary data analysis which explores the dynamics that enframe the making, transformation and state of the Turkish electricity market. The thesis illustrates that the most important determinant in the construction, establishment, maintenance, and consolidation of the Turkish electricity market is the active agency of the commodity itself. The analysis presents the ways in which, through the marketization process, not only the notion of the Turkish electricity market is constructed in terms of power relations in the exchange of electricity, but also how notions of the market, the economic, the social, and the political, as well as the conceptualization of individual and nature are recoded and transformed. It demonstrates that there is no economy without electricity, and no politics without economics within the current marketization process in Turkey.
Keywords: Electricity -- Turkey.; Electric utilities -- Turkey -- Costs.; Electric power consumption -- Turkey.; Energy industries -- Turkey.; Energy policy -- Turkey.